The effect of hard coal activities on space production-Zonguldak ?z?lmez Valley - Arslan, Nazli; Kerestecioglu, Server Funda (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2023)
According to his studies on the production of space, Lefebvre mentions that each production method produces a new type of space, and this production rises on three constituent feet. Different indicators in the perceived, conceived and living dimensions of the space are essential to understand the truth of the space and determining its potential and handicaps. Also, spaces with different histories have different production histories in line with their living dynamics. Considering that each space has its own production history, the necessity of evaluating the production in the mining city with underground and ground distinguishes these settlements from the others. Production targets shape the required workforce, the workforce shapes the infrastructure and superstructure demands, and the infrastructure and superstructure demands shape the morphological structure. This study aims to reveal the relationship between space and meta production in the coal production city Zonguldak. Based on space production and related theories, the space production periods and space triad of Zonguldak have been determined. As Lefebvre mentioned, the deepening contradictions of abstract space have revealed the contradictory space period. The contradictions that exist in Zonguldak are based on the tense relationship between underground hard coal production techniques and space production shaped by changing policies on the ground. Therefore, from the past to the present the contradictions and tense relationship between meta and space production in Zonguldak have been explained through specific examples of the city. In conclusion, the change of meta and space production, which continues at different scales on the ground and underground, is explained through specific variables and conceptual and physical tensions that occur on the surface of the city are defined.
Keywords: Production of space; production of hard coal; spatial contradictions; ?z?lmez Valley; Zonguldak; Architecture